2018
DOI: 10.1186/s13014-018-1126-7
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiation therapy for definitive treatment of cervical cancer: a meta-analysis

Abstract: BackgroundTo compare the efficacies and toxicities of intensity-modulated radiotherapy (IMRT) with three-dimensional conformal radiotherapy (3D-CRT) or conventional two-dimensional radiotherapy (2D-RT) for definitive treatment of cervical cancer.MethodsA meta-analysis was performed using search engines, including PubMed, Cochrane Library, Web of Science, and Elsevier. In the meta-analysis, odds ratios (ORs) were compared for overall survival (OS), disease-free survival (DFS), and acute and chronic toxicities.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 23 publications
(21 reference statements)
3
64
1
1
Order By: Relevance
“…A multi-institutional study evaluating the toxicity and survival outcomes after IMRT in 111 patients reported a 3-year OS rate of 78% and 3-year DFS rate of 69%. 19 Recently, a meta-analysis of six studies conducted by Lin et al 20 compared the efficacies and toxicities of IMRT with conventional RT for radical treatment of cervical cancers. They concluded there was no significant difference between 3-year OS and DFS, but toxicities were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-institutional study evaluating the toxicity and survival outcomes after IMRT in 111 patients reported a 3-year OS rate of 78% and 3-year DFS rate of 69%. 19 Recently, a meta-analysis of six studies conducted by Lin et al 20 compared the efficacies and toxicities of IMRT with conventional RT for radical treatment of cervical cancers. They concluded there was no significant difference between 3-year OS and DFS, but toxicities were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded there was no significant difference between 3-year OS and DFS, but toxicities were significantly reduced. 20 …”
Section: Discussionmentioning
confidence: 99%
“…has become more and more common 22,23 . Our data cannot assess whether IMRT and 3D-CRT will increase the risk of second primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective randomized trials and one meta-analysis demonstrated that the toxicities of IMRT were lower than that of conformal radiation therapy in patients with LACC treated with definitive radiation therapy ( 48 51 ). In the study by Gandhi et al ( 51 ), 44 patients with 2009 FIGO stage IIB-IIIB cervical cancer were randomized to receive whole pelvic conventional radiation therapy or IMRT.…”
Section: The Toxicities Of Efimentioning
confidence: 99%